1999
DOI: 10.1136/pgmj.75.881.154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the one-minute ultra-rapid urease test for diagnosing Helicobacter pylori

Abstract: SummaryTo determine the diagnostic accuracy of the one-minute ultra-rapid urease test for diagnosing Helicobacter pylori infection, two biopsies were taken from both the gastric corpus and antrum from 1000 patients undergoing upper gastrointestinal endoscopy. All the biopsies were subjected to the one-minute ultra-rapid urease test before imprint smears were prepared from them. Thereafter, the biopsies were fixed in 10% formalin and histological sections were examined for the presence of H pylori by a patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The H. pylori prevalence found in this study is comparable with that reported in earlier investigations [1,6,25]. The H. pylori re− sults were positive in approximately 25 % of the patients in both groups (20.4 % with HUT and 30.2 % with GBT; n. s.), correspond− ing to known prevalence rates of H. pylori for populations in Switzerland (24 %) [26,27] and western Europe (7 ± 54 %) [5] in patients of comparable age and socio−economic status [5,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…The H. pylori prevalence found in this study is comparable with that reported in earlier investigations [1,6,25]. The H. pylori re− sults were positive in approximately 25 % of the patients in both groups (20.4 % with HUT and 30.2 % with GBT; n. s.), correspond− ing to known prevalence rates of H. pylori for populations in Switzerland (24 %) [26,27] and western Europe (7 ± 54 %) [5] in patients of comparable age and socio−economic status [5,26,27].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, biopsies from five predetermined sites in stomach were taken from each patient to approach the correlation among H. pylori distribution, mucosa inflammation, gland type and age in different areas of stomach. Misra et al have shown the utility of using the same biopsy specimen for two tests [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upper gastro‐intestinal endoscopy was carried out, findings were recorded, and biopsy specimens taken from the antrum were fixed in 10% formalin for histologic examination and detection of H. pylori by half‐Gram stain. The rapid urease test was carried out in the antral biopsy as per the method mentioned in earlier studies using the test 15 …”
Section: Methodsmentioning
confidence: 99%
“…The rapid urease test was carried out in the antral biopsy as per the method mentioned in earlier studies using the test. 15 Serological examination for determination of H. pylori infection included determination of immunoglobulin G (IgG) antibody levels for H. pylori. ‡ A value ‡40 IU/ml was taken as positive and <40 IU/ml was taken as negative.…”
Section: Methodsmentioning
confidence: 99%